1997
DOI: 10.1182/blood.v90.10.3893
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human Interleukin-11 Directly Promotes Megakaryocytopoiesis In Vitro

Abstract: We have investigated the mechanism of action of the thrombopoietic cytokine, recombinant human interleukin-11 (rhIL-11), on megakaryocytopoiesis in vitro. We have shown that rhIL-11–induced murine and human megakaryocytopoiesis are not mediated by thrombopoietin (Tpo). Murine megakaryocytes (MKs) were produced from bone marrow (BM) mononuclear cells cultured with rhIL-11, IL-3, and a combination of the two cytokines. Conditioned media (CM) were collected and assayed for the presence of biologically active Tpo.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…When IL-11 receptors are stimulated by ligand binding (Figure 2a), they undergo phosphorylation and activate the STAT3 transcription factor. 54 IL-11 promotes megakaryocyte maturation, stimulates platelet production in normal animals, and can enhance haematopoietic recovery following myelosuppression. In mice, IL-11 increased megakaryocyte ploidy in the bone marrow and megakaryocyte colony-forming units (CFUs) in the spleen.…”
Section: Il-11mentioning
confidence: 99%
See 1 more Smart Citation
“…When IL-11 receptors are stimulated by ligand binding (Figure 2a), they undergo phosphorylation and activate the STAT3 transcription factor. 54 IL-11 promotes megakaryocyte maturation, stimulates platelet production in normal animals, and can enhance haematopoietic recovery following myelosuppression. In mice, IL-11 increased megakaryocyte ploidy in the bone marrow and megakaryocyte colony-forming units (CFUs) in the spleen.…”
Section: Il-11mentioning
confidence: 99%
“…10,[55][56][57][58] Interestingly, the IL-11 receptor is not present on platelets. 54 Clinically, recombinant human IL-11 (rhIL-11; oprelvekin) has been successful in some patients. In a phase I study in advanced breast cancer patients treated with myelosuppressive chemotherapy, treatment with rhIL-11 produced dose-dependent increases in bone marrow progenitor cells, megakaryocytes and mean platelet counts.…”
Section: Il-11mentioning
confidence: 99%
“…It is encoded by a single gene on chromosome 19 and is normally produced in bone marrow stromal cells. Receptors for IL‐11 are found on a large number of cell types, including osteoblasts, osteoclasts, intestinal crypt cells, oral mucosa cells, B‐lymphocytes, and megakaryocytes, but not in platelets 23–25 …”
Section: Pgfsmentioning
confidence: 99%
“…IL‐11. Although IL‐11 was initially found to stimulate proliferation of an IL‐6‐dependent murine plasmacytoma line, 23–25 subsequent work showed that it had a wide range of activities, often in combination with other hematopoietic growth factors. IL‐11 promoted the growth of immunoglobulin‐secreting B cells in vitro.…”
Section: Biologic Effects Of Pgfsmentioning
confidence: 99%
“…Interleukin-11 (IL-11) was originally identified as a stromal cell product that stimulated proliferation of IL-6-dependent plasmacytoma cells [1]. Subsequent studies have demonstrated that IL-11 has effects similar to IL-6, including megakaryocyte proliferation [2] and induction of acute phase response proteins [3]. Functional similarities between IL-6 and IL-11 can be explained by the fact that signal transduction for both of these cytokines is mediated through the transmembrane glycoprotein 130 (gp130) receptor component, which is common to both IL-6 and IL-11 receptor complexes [4,5].…”
Section: Introductionmentioning
confidence: 99%